Analisa Pengaruh Absorpsi Air Laut Terhadap Kekuatan Tarik Komposit Serat Pelepah Sawit - Zulkifli, Zulkifli; Hermansyah, Hadi; Syahruddin, Syahruddin (Politeknik Negeri Ujung Pandang, 2017)
This study aims to analyze the absorption of sea water on Composite Materials palm frond fibers per 24 hours for 9 days and analyze the effect of immersion for 3, 6, and 9 days of the tensile strength fiber-reinforced composite material of palm fronds. The polymers used type of epoxy resin. Palm frond fibers arranged randomly, then fiber treated alkali 5% for 2 hours, and then molded with a size of 200 x 200x 5 mm with a ratio between matrix and fiber is 90:10 to press molding tool. Composite plates immersed in a container filled with sea water aquarium for 3, 6, and 9 days and every 24 hours of material in weigh, test procedures seawater absorption refers to the ASTM D 570 - 98. As well as every 3, 6, and 9 days plate removed and cut into a polymer composite beam according to the standard ASTM D638-02 (type 1). Each variable will be tested for 3 times. Based on the test results get soaking in the absorption rate reached its peak in the first day, namely 0.26% for the first specimen testing three-day, 0.5% for the second specimen testing 6 days and 0.25% for the third specimen testing nine days. Then it will go on steadily and decreases until it reaches saturation point. Where for the first specimen in the third day of absorption of 0.49%, a second specimen in the sixth day of absorption of 1.71%, and the third specimen in the esembilan absorption 0.93%. And the influence of sea water immersion tensile strength fiber Composite palm fronds have a dynamic effect on the test results before immersion up to 9 days of immersion that is power up and down. With a value of 15.468 MPa before immersion, 17.046 MPa 3 days of immersion, 15.107 MPa 6 day immersion, and 21.137 MPa 9 days of immersion.